2020
DOI: 10.1101/2020.01.11.901751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imidacloprid Movement into Fungal Conidia is Lethal to Mycophagous Beetles

Abstract: 1. Applications of systemic pesticides can have unexpected direct and indirect effects on nontarget organisms, producing ecosystem-level impacts. 2. We investigated whether a systemic insecticide (imidacloprid) could be absorbed by a plant pathogenic fungus infecting treated plants and whether the absorbed levels were high enough to have detrimental effects on the survival of a mycophagous beetle. Beetle larvae fed on these fungi were used to assess the survival effects of powdery mildew and imidacloprid in a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The persistence of systemic insecticides in tissues of plants and fungi becomes a death trap for non-target mycophagous insects such as the twenty-spotted ladybeetle, Psyllobora vigintimaculata (Coleoptera: Coccinellidae), which feeds on conidia and hyphae of powdery mildews (Erysiphales). These pathogenic fungi grow on the treated plants and act as reservoirs of the insecticides applied (i.e., imidacloprid), indirectly poisoning the ladybugs that are the natural control of the fungi [ 83 ]. Similarly, systemic insecticides can adversely affect predatory bugs such as Orius insidiosus (Hemiptera: Anthocoridae), which often feed on plant sap [ 84 ], and the lacewing Chrysoperla carnea (Neuroptera: Chrysopidae), which also feeds on extra-floral nectar containing residues [ 85 ].…”
Section: Indirect Effects In Terrestrial Ecosystemsmentioning
confidence: 99%
“…The persistence of systemic insecticides in tissues of plants and fungi becomes a death trap for non-target mycophagous insects such as the twenty-spotted ladybeetle, Psyllobora vigintimaculata (Coleoptera: Coccinellidae), which feeds on conidia and hyphae of powdery mildews (Erysiphales). These pathogenic fungi grow on the treated plants and act as reservoirs of the insecticides applied (i.e., imidacloprid), indirectly poisoning the ladybugs that are the natural control of the fungi [ 83 ]. Similarly, systemic insecticides can adversely affect predatory bugs such as Orius insidiosus (Hemiptera: Anthocoridae), which often feed on plant sap [ 84 ], and the lacewing Chrysoperla carnea (Neuroptera: Chrysopidae), which also feeds on extra-floral nectar containing residues [ 85 ].…”
Section: Indirect Effects In Terrestrial Ecosystemsmentioning
confidence: 99%
“…However, it has been shown that when the stressor is stopped, the organisms recover without any long-term effects [51]. For the first time, researchers have documented the tritrophic movement of imidacloprid from plants to fungi to insects, resulting in a significant number of indirect deaths of non-target mycophasimilar beetles, and adversely affecting an important set of pathogen biological control pathways [52]. Compared to other non-target aquatic insects, neonicotinoid insecticides cause less harm to the early-life stages of the ramshorn snail and Planorbella pilsbryi [53].…”
Section: Toxicity To Insectsmentioning
confidence: 99%